Practical Implementation of Contract Administration Performance Model in Qatar Construction Projects - Gunduz, Murat; Elsherbeny, Hesham A. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Globally, the performance of Construction Contract Administration (CCA) is becoming of significant interest as the industry suffers from notable delays, cost overruns, and disputes as a consequence of poor contract administration practices. In Qatar, the pace of projects will continue after hosting the FIFA 2022 World Cup to achieve the 2030 Qatar National Vision and beyond, therefore, monitoring of the proper CCA implementation and performance is necessary. Due to the wide scope and complicated nature of CCA, there is yet no consensus on how to assess its performance. This study briefly presents a systematic, operational, and multi-dimensional construction Contract Administration Performance Framework (CAPF) consisting of 93 CCA key measures/ tasks categorized in 11 CCA dimensions/process groups. The proposed framework is validated by structural equation modeling and subsequently, the Contract Administration Performance Model (CAPM) model was established. Through this study, the CAPM and its components are briefly explained, and then implemented on a real-world sample of 13 small, medium, and major construction projects in Qatar covering both public and private sectors, and then the performance is benchmarked. It is found that the model provides an operational basis for measuring the CCA Group Performance Indices (GPI), the overall Construction Contract Administration Performance Index (CCAPI) and support the identification of underperforming groups. The benchmarking value for the CCAPI (77.5%) demonstrates that the level of CCA performance is good. Also, the benchmarking values of GPI (range 74.3% to 87.8%) are good, except risk management (GPI= 50.5%), which needs an improvement program.